Microtrabalho no Brasil: gestão algorítmica e precarização na plataforma Amazon Mechanical Turk - Vasconcelos, Thaís Lopes (2024)
This dissertation presents the results obtained from research carried out on the precariousness of work within the scope of platform capitalism, focusing on microwork on the Amazon Mechanical Turk platform in Brazil. It aims to analyze how the objective conditions of precariousness that characterize microwork on the Amazon Mechanical Turk platform are pointed out in the literature and perceived by workers in a group on the instant messaging application (Telegram). The assumption supported by the investigation is that, given the process of restructuring relations between capital and labor, platforms are the service industry of our time and the company Amazon is emblematic of this new operating mode in the world of work, which is based on flexibility and precariousness. To reach this conclusion, we start from the debate on the use of new technologies in platform capitalism, as a concrete materiality of the object of study. Regarding the methodological approach, this is an exploratory research with a qualitative approach. To achieve our objectives we resorted to a combination of bibliographic and documentary research. The research develops a trend that appears in research already carried out on microwork, which is precariousness, focused on the following aspects present in working conditions, such as dismantling in organizational forms; lacking control over work management; devoid of rights and regulation; intensification of labor exploitation and intensification of outsourcing and informality. The documentary research analyzes Amazon documents, YouTube videos with platform workers and messages from workers, available on the Telegram application, over a period of 6 months. The exploratory nature of the research allowed us to formulate the following conjectures about microwork on the Amazon Mechanical Turk platform in Brazil: the perception of workers is permeated with neoliberal discourse; workers perceive the salary as a supplement to their income and a flexible working day as a worker's responsibility; workers do not understand how work management works using algorithms; communication between workers and the platform is inefficient and the data indicates that this condition is proposed for the platform; the messaging group on Telegram works as a form of resistance; workers look for ways to subvert platform control; There are differences in treatment for Brazilian workers based on the international division of labor.